Grammatical Errors in the “Portal Nasional Republik Indonesia” Website - Agustina Ganda Harta Sinaga (Universitas Gadjah Mada, 2014)
This research aims at investigating the grammatical errors that occur in the English version of an official Indonesiawebsite “Portal Nasional Republik Indonesia”. In particular, it attempts to classify the errors based on Surface Strategy Taxonomy proposed by Dulay, Burt, and Krashen (1982). The data used in this research are taken from four articles on the website,: Indonesia at a Glance, President & Vice, United Indonesia Cabinet, and Palaces. The result shows errors in sixteen linguistic categories in the Surface Strategy Taxonomy which are divided into: omission, addition, misformation, and misordering. From all the four parts, the most frequent errors are in the part of misformation (188 errors; 78.96%) followed by omission (39 errors; 16.38%), addition (8 errors; 3.36%), and misordering (2 errors; 0.84%). From the linguistic categories, the three most frequent errors are the “spelling” with 74 errors (31.08%), then “parallelism” with 62 errors (26.04%), and “determiner” with 21 errors (8.82%). The research concludes that the author needs to develop his accuracy in using english in order to keep the reputation of the website.